Effect of Eight-week Core Stabilization Exercises on Static and Dynamic Balance Indices in Girls with Hyperlordosis: A Controlled Laboratory Study - Farideh Babakhani; Mohamadreza Hatefi; Mohadeseh Ashrafizadeh; Masoud Barzegar (Shiraz University of Medical Sciences, 2020)
Background: Postural control can be affected by hyperlordosis and the effect of core training on postural control has yet to be established in students with hyperlordosis. Therefore, the aim of this study was to investigate the effect of core stabilization exercises on balance indices in girls with hyperlordosis. Methods: In this controlled laboratory study, we divided 32 girls (14-15 years old) with hyperlordosis inTehran schools into experimental and control groups in 2018. The experimental group received two core exercise sessions per week for a period of eight weeks. Before and after exercises, we evaluated the balance indices of center of pressure (COP) and time to stabilization (TTS). To analyze the data, statistical analysis of the t-test was used via SPSS software. Results: We observed significant differences in the COP indices of R.AP (P=0.038) and V.AP (P=0.001) and TTS indices of vertical (P=0.012), antroposterior (P=0.032), and mediolateral directions (P=0.001) before and after stability exercises in the experimental group; however, no significant difference was found in R.AP (P=0.221), R.ML (P=0.192), V.AP (P=0.461), and V.ML (P=0.195) in the control group. Furthermore, the results implied a significant difference in the COP indices of R.AP (P=0.001) and V.AP (P=0.023) and the TTS indices of vertical (P=0.001), antroposterior (P=0.001), and mediolateral directions (P=0.001) between the two groups in the post-test condition. Conclusions: The study findings revealed that the eight weeks of core stabilization exercises could be considered as an appropriate training method for improving the postural control for 14-15-year-old girls with hyperlordosis.